Catalytic asymmetric construction of spiro[pyrrolidine-2, 3′-oxindole] scaffolds through chiral phosphoric acid-catalyzed 1, 3-dipolar cycloaddition involving 3-amino oxindoles. Issue 85 (8th September 2015) - Zhu, Guodong; Wang, Baomin; Bao, Xiaoze; Zhang, Huanrui; Wei, Qian; Qu, Jingping
Abstract : The catalytic asymmetric three-component 1, 3-dipolar cycloaddition of 3-amino oxindoles with aldehydes and nitroolefins with a chiral phosphoric acid is reported. Abstract : The catalytic asymmetric three-component 1, 3-dipolar cycloaddition of 3-amino oxindoles with aldehydes and nitroolefins under the catalysis of a chiral phosphoric acid is reported. The reaction provides a facile approach to synthesize a diverse array of spiro[pyrrolidine-2, 3′-oxindoles] in high yields with excellent diastereo- and enantioselectivities under mild conditions.